SDN-assisted technique for traffic control and information execution in vehicular adhoc networks. (September 2022) - Tao, Hai; Zain, Jasni Mohamad; Band, Shahab B.; Sundaravadivazhagan, B.; Mohamed, Abdullah; Marhoon, Haydar Abdulameer; Ogbonnia, Otuu Obinna; Young, Praise
Abstract: Recently, applying Software-Defined Networking (SDN) in automotive industry has sparked a lot of interest due to its capacity to ensure focused organization across the board coupled with its vast versatility of isolating data from the control plane. However, the major concern in traffic network is that varied crisis and diversion messages are expected to be shared or brought into by the connected vehicles. Thus, disclosure of this information results in an evaluation of the steering and control of such messages. This research aims at employing SDN-assisted technique in heterogeneous vehicular organizations in executing information traffic-using optimal course determination and guiding in situations like a blockage in Vehicle Ad Hoc Networks (VANETs). To realize this, a workable traffic reproduction model is proposed and the experiments realized a re-enactment findings in terms of Round Trip Time (RTT) and Packet Delivery Ratio (PDR) and improves the conventional information flow structure.